The Education of the Handicapped Amendments of 1986. Hearings before the Subcommittee on Select Education of the Committee on Education and Labor. House of Representatives, Ninety-Ninth Congress, Second Session on S.2294, the Education of the Handicapped Amendments of 1986 (July 23, 24, and 29, 1986) - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Testimony is presented regarding the Education of the Handicapped Amendments of 1986 which mandates special education for handicapped children from the age of 3 and proposes a discretionary program of infant intervention. Testimony from the following agencies and associations is included: National Association of State Boards of Education; National Center for Clinical Infant Programs; Alexander Graham Bell Association for the Deaf; Consortium for Citizens with Developmental Disabilities; United Cerebral Palsy Associations, Inc.; American Speech-Language-Hearing Association; Epilespy Foundation of America; House Select Committee on Children, Youth and Families; National Association of State Directors of Special Education; National School Boards Association; Association for Retarded Citizens; American Association of School Administrators; National Governors Association; National Indian School Boards Association; American Federation of Teachers; National Conference on State Legislatures; National Society for Children and Adults with Autism; Council for Exceptional Children; Federation for Children with Special Needs; American Rehabilitation Counseling Association; American School Counselor Association; National Association of Elementary School Principals; American Rehabilitation Counseling Association; American Mental Health Counselors Association; National Council on the Handicapped; National Association of Secondary School Principals; National Education Association; United States Department of Education; and National Network of Parent Centers. (CB)
ERIC Note: Serial No. 99-120. Parts of the document have small type.
Educational level discussed: Higher Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Educational Legislation; Educational Needs; Federal Legislation; Hearings; Higher Education; Infants; Intervention; Preschool Education; Public Education; Special Education; Early Intervention -- Education of the Handicapped Amendments 1986; Congress 99th; Legal/Legislative/Regulatory Materials